2019
DOI: 10.3389/fpsyg.2019.00366
|View full text |Cite
|
Sign up to set email alerts
|

Grieving for Job Loss and Its Relation to the Employability of Older Jobseekers

Abstract: Introduction: Loss of employment is an experience that is lived and interpreted differently depending on a series of individual variables, including the psychological resources available to the affected person as well as their perception of their degree of employability. Losing one’s job can be one of the most painful and traumatic events a person has to withstand. Following a dismissal, the worker needs to overcome a period of emotional adaptation to the loss. But that period of grieving can also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
0
8
0
3
Order By: Relevance
“…One's subjective perception of the difficulties or obstacles that one could encounter during the job-seeking process is also closely related to one's perceived employability [38]. The struggle of an individual in believing in his/her chances of finding employment, while not consistent with facts, can play a specific reactive predictive role [39].…”
Section: Emotional Regulation and Perceived Employabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…One's subjective perception of the difficulties or obstacles that one could encounter during the job-seeking process is also closely related to one's perceived employability [38]. The struggle of an individual in believing in his/her chances of finding employment, while not consistent with facts, can play a specific reactive predictive role [39].…”
Section: Emotional Regulation and Perceived Employabilitymentioning
confidence: 99%
“…Among the different taxonomies of factors affecting an individual's employability, central roles are attributed to work centrality, values and goals; availability, adaptability, and difficulties in finding a job; attitudes and fears about the unemployment situation and the search for a new job [38,40].…”
Section: Emotional Regulation and Perceived Employabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of longitudinal studies has shown that job loss can cause severe emotional distress (Paul & Moser, 2009 ). Job loss may yield transient reactions of grief (Brewington, Nassar‐mcmillan, Flowers, & Furr, 2004 ; Climent-Rodríguez, Navarro-Abal, López-López, Gómez-Salgado, & García, 2019 ; Diaz et al, 2015 ; cf. Lorenz, Maercker, & Bachem, 2020 , who focused on adjustment disorder after involuntary job loss).…”
Section: Introductionmentioning
confidence: 99%
“…What may be more difficult to manage, however, are the emotional resources needed to navigate the transition to retirement. In particular, the inevitable loss of self‐identity may lead to anticipatory grief and bereavement 13 . That intending to retire is viewed as a mark of ageing less well by practitioners not only poses a considerable challenge for their retirement planning, but highlights the importance of understanding successful ageing in any discussion of transitioning away from full‐time work in medicine.…”
Section: Resource Accumulationmentioning
confidence: 99%